Humanism and Constructivism Learning Theories (Their Application in Islamic Religious Education Learning) - Herman Darmawan; M. Ramli (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2025)
Humanistic learning theory emphasizes the importance of human aspects in the educational process. Meanwhile, constructivism focuses on the process of how students build knowledge and understanding through experience and interaction with their environment. Both of these theories are essential for educators to understand as a foundation for implementing learning activities. Based on previous research, it seems that there has been no research that examines Humanism and Constructivism Learning Theories (Their Application in Islamic Religious Education Learning) especially literature review research. The purpose of this study is to identify and highlight several publications that examine how humanism and constructivism learning theories (their application in islamic religious education learning). This research uses a literature review, where data is collected from scholarly writings or literature. The findings indicate that in humanistic learning theory, this approach encourages educators to consider students' needs, interests, and motivations, making the learning process more personal and meaningful. Meanwhile, constructivist theory helps students connect religious teachings to daily life, making the material more relevant and applicable. The integration of both theories in Islamic Religious Education (PAI) learning practice can create a holistic learning experience. This will contribute to the development of strong character and deep spiritual understanding in students.